Relationship between Intellectual Intelligence and Learning Motivation with Learning Achievement - Danang Prihandoko; Jerry Sendi; Devisya; Mary Petrina; Stecy Novrisa (International Journal of Organizational Business Excellence, 2023)
The research was conducted with the aim of finding out which factors have the most significant relationship with increasing student learning achievement. The method used in this research is an explanatory research method with an approach method, namely a survey by giving questionnaires to respondents. The results of the research show that there is a relationship between intellectual intelligence and learning motivation on learning achievement using the validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, multiple linear regression test, coefficient of determination test, f table test, and t table test with levels of 95% confidence and SPSS version 25. The SPSS output related to the variables intellectual intelligence and learning motivation obtained a tolerance value of 0.363, greater than 0.05, and was supported by a VIF value of 2.754, smaller than 10. Based on the research results, there is a positive relationship between intellectual intelligence, learning motivation, and learning achievement in students.